Processed fruits and vegetables industry - "Uday Sekhar, A." (New Delhi, 1994)
One of the principal objectives of the economic reforms initiated in 1991 is to bring about rapid industrial growth through private sector investment (as in the case of agriculture) and to make Indian Industry internationally competitive, increase exports and participate in the global economy. When government withdraws largely from direct investment in Industry, from allocation of resources in industry, through licensing and related measure, and from protection through import substitution, the question arises whether government has a role to play in the future growth of industry, apart from ensuring macro-economic stability, a fairly high rate of savings in the economy, access to foreign capital and technology, heavy investment in human capital and a sound and efficient financial system.
Keywords: Vegetables industries